Pembelajaran Berdiferensiasi dalam Perspektif Progresivisme pada Mata Pelajaran IPA - Devi Kurnia Fitra (Undiksha, 2022)
This research aims to describe John Dewey's Progressivism towards differentiated learning, aswell as the application of differentiated learning to science subjects. This research method is aliterature study based on books and scientific journals that discuss progressivism, differentiatedlearning and the application of differentiated learning in science subjects. The data obtained from the Pustaka study are synthesized into meaningful information. The purpose of this study is to describe the relationship between the flow of progressivism with differentiated learning, as wellas the application of differentiated learning to science subjects in junior high schools based onjournal references. Progressivism is an educational perspective that supports an educational process that favors students and that learning is always evolving throughout the ages.Differentiated learning is learning based on student learning needs consist of learning readiness, student learning profiles, interests and talents. Differentiated learning can be implemented in several ways, including: content differentiation, process differentiation, product differentiation and learning environment. Although it is not new in education, the application of differentiated learning in science learning is only limited to measuring learning outcomes.